Characteristics of air pollution variation and potential source contributions of typical megacities in the Sichuan Basin, Southwest China - Li, Xiaoju; Abdullah, Luqman Chuah; Sobri, Shafreeza; Syazarudin, Mohamad; Aslina Hussain, Siti; Poh Aun, Tan; Hu, Jinzhao (Springer, 2023)
Air pollution is a regional issue, influenced not only by local emission sources but also by regional transport. This study excavated the pollution variation of PM2.5 and O3 from 2014 to 2020 through statistical analysis in the megacity-Chengdu. Then, based on backward trajectory calculation and trajectory clustering, the long-term air mass transport pathways were explored, and the Potential Source Contribution Function (PSCF) model and Concentration Weighted Trajectory (CWT) analysis method were combined to further quantitatively identify the potential source areas affecting PM2.5 and O3 from an annual perspective. Finally, suggestions and measures for synergistic control of O3 and PM2.5 are put forward. The results showed that the CWT simulation results were basically consistent with the PSCF simulations, and there were significant inter-annual differences in the potential contributing source areas of pollutants. PM2.5 and O3 concentrations are not only affected by local source emissions, but regional transport (Chongqing, Lanzhou, Xi’an) is also an important source of contribution. In addition, the proportion of PM2.5 pollution trajectories decreased from 30% in 2015 to 12% in 2020, while the proportion of O3 pollution trajectories fluctuated. This study provides more detailed information on potential source regions of pollutants in typical megacities, better captures their spatial heterogeneity, and highlights the role of local sources and transboundary transport. More importantly, it also accumulated some experience for regional joint prevention and control air pollution in China’s megacities and other similar situations in the world.